Human remains from Geula Cave, Haifa - Baruch Arensburg (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
Three human skeletal fragments were unearthed by Wreschner during archaeological excavations in the Mousterian cave of Geula, in Haifa, during the years 1958-1964. The remains and especially the frontal bone belong, according to their morphology, to an ancient Homo sapiens. These finds enhance the long term discussion on ancient sapiens and so-called Neanderthal relationships in the Levant.